Cage-like crystal packing through metallocavitands within a cobalt cluster-based supramolecular assembly. Issue 19 (19th April 2018) - Kang, Philjae; Mai, Hien Duy; Yoo, Hyojong
Abstract : The generation of cage-like crystal packing geometry of TSHs in the solid state induced by the host–guest interactions among metallocavitands. Abstract : A cobalt (Co) supramolecular triple-stranded helicate, [Co8 (PDA)6 ( Br -PTA)3 (DMF)4 (H2 O)2 ] (1 ) (PDA = 2, 6-pyridinedicarboxylate, Br -PTA = 5-bromoisophthalate, DMF = dimethylformamide), is successfully synthesized and fully characterized. The solid-state structure of1 shows that four cobalt atoms are coordinated by three PDA ligands to form a tetranuclear cobalt cluster with three extension points and the ditopic Br -PTA ligands interlink two basic assembly units. In crystal packing, the bromo group is surrounded by the cavity-like tetranuclear cobalt cluster, which acts as a metallocavitand, to generate a unique cage-like crystal packing geometry. The isomorphous molecular cage, which exhibits a similar crystal-packing geometry as observed in1, is also successfully isolated. This is an unusual example of a highly symmetric cage-like crystal packing architecture, resulting from the interaction among metallocavitands of in situ generated supramolecular modules.